Parking policy: The socio-legal architecture of parking bays in American cities. (February 2020) - Marusek, Sarah
Highlights: First, I have made the distinction between the colloquial/social and legal meanings of 'property' in the paper. Second, I have incorporated Dorsett and McVeigh's work on jurisdiction. Lastly, I have removed the italics from the case. Abstract: In Western vehicularized society, we are constructed by lines. We wait in queues while stuck in traffic, waiting for a morning coffee, even to receive basic governmental entitlements. Lines perpetuate order in an otherwise world of chaos. Lines frame how we distinguish between order and chaos. In parking, lines frame a legitimized rectangle of vehicular occupancy. In other words, the marked parking space is ours for a little while *if* we park within the lines. The legal aesthetic of lines designating parking spaces on pavement symbolizes a legal landscape of cars and people. This performance of law that keeps us 'in line' is a really a construction of order designed according to the spatiality of belonging (Philippopoulos-Mihalopoulos, 2015 ). Whether on streets or in lots, pavement that is painted for parking is a site of legal culture. This material spatialization perpetuates a map of life based upon vehicular size and designated usage. The cultural architecture of these lines spatially engenders the paved environment (Dovey, 2009 ; Lefebvre, 1991 ) and generates a form visual legal pollution that further contributes to the nomospheric occupancy of place in everyday life (Delaney, 2010 ). Yet, everyday resistance to such linear normativity (Barr, 2015 ) disrupts the normative ordering of place and tests the socio-legal imagination.